Transcranial Direct Current Stimulation Combining Mindfulness Based Relapse Prevention for Smoking Cessation: A Case Report - Khayyer, Zahra; Saberi Azad, Razieh; Dadjoo, Mohsen; Shojaei, Azam (International Clinical Neuroscience Journal, 2019)
Previous electroencephalography (EEG) researches have shown significant differences in terms of abnormal brain activity among smokers and non-smokers. Typically, EEG analysis showed decreased slow waves and increased fast waves in people with nicotine consumption. The present study tested a transcranial direct current stimulation (tDCS) technique combined with Mindfulness-Based Relapse Prevention (MBRP) to reduce nicotine cravings. Specifically, cathodal tDCS over Left Prefrontal Cortex (PFC), as well as anodal stimulation over the right central zone, tested. An 18-year-old right-handed male with almost three years of smoking participated. He had no anti-tobacco medical prescription. The participant received twelve sessions of tDCS treatment (two times a week). Anodal stimulation (1.5 mA, 15 min) performed on C3 (LORETA source localization) and cathodal stimulation on FP2. Also, the participant received 30-minute MBRP-based psychotherapy sessions in order to ameliorate aggression, stress, and craving. Clinical evaluations, Buss-Perry Aggression Questionnaire (AGQ), Fagerstrom Test for Nicotine Dependence (FTND), Perceived Stress Scale (Cohen, Kamarck, & Mermelstein, 1994), and daily checklist for the number of smoked cigarettes administered along with Carbon monoxide (CO) levels. Also, subjective measures of craving intensity between zero and ten measured after treatment and 3-month follow-up. After treatment, the participant showed a substantial reduction in all clinical tests, and the number of cigarettes decreased from 30 to 2 a day. From a psycho neurotherapeutic perspective, the present study provides preliminary indications for a novel and efficient treatment of smoking during adolescence. Further studies are needed to determine generalizability and overall efficiency.